Boardrooms and firm performance. - Tan, Cedric. (2008)
This research examines firms' various board characteristics and directors' attributes which may affect the firms' decision to adopt the Code of Corporate Governance since it became compulsory. The value relevance of board characteristics and directors' attributes was further examined against firm performance.